Legal Protection of Online Investors on the Binomo App by Alert Task Force Investment Financial Services Authority - Suwandi Suwandi; Kusno Kusno; Toni Toni (Journal of Social Research, 2022)
Background: Broadly speaking, an investment is a commitment to a certain amount of funds or other resources such as equipment, immovable assets, intellectual property rights, or expertise. Investments are made personally as well as by legal entities. Investment in general, has several objectives, the first, is to get a more decent life in the future, the second is to reduce inflationary pressures, and the third is to save taxes. Objective: This study aims to find out as well as analyze the legal protection of online Investors on the Bonomo application by the investment alert task force of the financial services authority. As well as knowing and analyzing about. Methods: This research belongs to the normative type of research. So it can be known that the legal protection of investors by brokerage companies has not been sufficiently able to accommodate the interests of investors. Result: In Law Number 21 of 2011 concerning the Financial Services Authority (OJK Law), the authority and duty of the OJK are to supervise Financial Services Institutions (LJK) in the capital market sector, the non-bank financial industry sector (such as insurance, pension funds, financing companies, etc.) and starting in 2014 will also supervise the banking sector (Commercial Banks and People's Credit Banks). Conclusion: Based on the above explanation, it can be concluded that the legal protection of investors by brokerage companies has not sufficiently accommodated the interests of investors.